Optimization of parameters of antimony modified carbidic austempered ductile iron (CADI) using Taguchi method. Issue 1 (1st January 2019) - Barnabas, Abel A.; Oyetunji, A.; Seidu, S. O.; Adediran, Adeolu A.; Igbafen, Emmanuel
Abstract: In this work, optimization of hardness, wear and impact strength of antimony modified CADI using Taguchi method was carried out. Carbidic Austempered Ductile Iron is a type of wear resistant ferrous metal having alloyed carbides inside an ausferritic matrix with an evidence of few graphite nodules in most cases. The alloy carbides which are mostly of primary coarse carbides are detrimental to its mechanical properties. The need for improvement of these mechanical properties (hardness, wear, and impact strength) in CADI has led to the usage of micro-addition of antimony to modify the carbides size which has given birth to Antimony Modified CADI. In a bid to get the optimum production factors on the mechanical properties, signal-to-noise (S/N) ratio was computed based on the design of experiments and the Straight graph of Minitab 17. The analysis of variance was computed to know the quantities of the contribution of factors on each mechanical property including its significance. From Taguchi analysis of the hardness, wear resistance and impact toughness, the signal-to-noise ratio using larger is better revealed that antimony content in the antimony modified CADI is the most important factor, followed by the austempering time in terms of improving the hardness and wear resistance of this material, while in the case of impact toughness, antimony content and austempering temperature are the most important factors, and that increasing these parameters would greatly improve the impact toughness of this CADI. The experimental values compared suitably with the results from Taguchi.